2014
DOI: 10.1186/s13028-014-0087-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the oral 13C-bicarbonate technique for measurements of energy expenditure in dogs before and after body weight reduction

Abstract: BackgroundOverweight and obesity are the most common nutritional disorders in dogs and may lead to various secondary diseases and decreased lifespan. In obesity research, measurement of energy expenditure (EE) and determination of the energy requirements are essential. The objective with this study was to validate and evaluate the suitability of the oral 13C-bicarbonate technique (o13CBT) for measuring EE in dog obesity studies. A further objective was to investigate the impact of body weight (BW) reduction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…It is well known that the recovery of 13 C is not complete, and in studies using IV administration of 13 Cbicarbonate the RF in breath CO 2 has been found to be 0.73 in young bulls (Junghans et al, 2007), 0.72 in goats (Prieto et al, 2001), and in studies with oral administration the RF was found to be 0.69 in humans (Junghans et al, 2008) and 0.72 in dogs (Larsson et al, 2014). In this study there was a significant difference between the two administration routes with a RF of 0.690 for IV and 0.760 for oral administration.…”
Section: Recovery Factor and Respiratory Quotientmentioning
confidence: 94%
See 3 more Smart Citations
“…It is well known that the recovery of 13 C is not complete, and in studies using IV administration of 13 Cbicarbonate the RF in breath CO 2 has been found to be 0.73 in young bulls (Junghans et al, 2007), 0.72 in goats (Prieto et al, 2001), and in studies with oral administration the RF was found to be 0.69 in humans (Junghans et al, 2008) and 0.72 in dogs (Larsson et al, 2014). In this study there was a significant difference between the two administration routes with a RF of 0.690 for IV and 0.760 for oral administration.…”
Section: Recovery Factor and Respiratory Quotientmentioning
confidence: 94%
“…Junghans et al (2007) used oral administration of 13 Cbicarbonate dissolved in water to humans and obtained satisfactory results when comparing the 13 C-BT to IC. In a study in dogs it was found that oral administration of 13 Cbicarbonate could be used to assess reliable estimates of EE (Larsson et al, 2014). In those two studies it was probably easier to control that the entire dose reached the stomach, as the humans drank a water solution with the dose and the dogs swallowed the dose mixed with a small amount of meat.…”
Section: Administration Routementioning
confidence: 97%
See 2 more Smart Citations
“…Results from this intervention have previously been published regarding effects on body composition, immunometabolic parameters, gene expression and energy expenditure (Larsson et al . ; Herrera Uribe et al . ; Vitger et al .…”
Section: Introductionmentioning
confidence: 99%